Laboratory study of the effect of the number of groin in the radial arrangement of permeable groin on the maximum scouring rate of the nose - Fateme Maleki; saeed abbasi; zahra maleki (مهندسی و مدیریت ساخت, 2023)
The scouring phenomenon is one of the issues that are always important in the design of various types of hydraulic structures; among these structures is the groin. These structures prevent their erosion by diverting the flow from the river bank. The flow mechanism in rivers at the locations of groin is such that the bed of a river undergoes changes and erosion over time. In this study, the performance of the permeable radial groin with different numbers was investigated. Also this groin was comparison with the double and single direct permeable arrangement. For this purpose, a flume with 5, 0.3, 0.3 meter long, wide and high was used, respectively. The experiments were conducted with a permeability rate of 40% in clear water conditions. The observations from the experiments regarding the maximum scour depth created in the flume bed show that the number of groin in a radial arrangement has an effect on the maximum scour hole depth.